Embalagem de maquiagem compacta: um estudo de acessibilidade para pessoas com deficiência visual - Maia, Guilherme Ferreira (Brasil, 2025)
The application of visual language in the design of beauty products to communicate specifications is an efficient alternative to make communication clearer and more dynamic. However, when used exclusively, it can create obstacles for individuals who do not use vision as their main means of perception and identification. This study aims to identify the points that make makeup packaging, especially compact products, inaccessible to people with visual impairments and gather information to facilitate the creation of inclusive elements in existing packaging on the market. Using the four stages of Löbach's methodology (2001) and the seven principles of Universal Design, the research, carried out empirically, proposes the creation of tactile identification in compact makeup products. As a result, a tactile identification subsystem was developed to be implemented on the packaging of a specific brand, without changing the visual identity of the product.